Efecto de la incorporación de tres tipos de almidones en las propiedades texturales de una carne vegetal - García Saltos, María Stephanie (2017)
The effect of the incorporation of three types of starches in the textural and organoleptic properties of a vegetable meat was evaluated, and the protein content was evaluated for the best treatment. Cassava, maize and potato starch were used in two percentages (5 and 10%). Textural properties were measured through the Shimadzu Texturometer; At a temperature of 25 + -1 ° C, with a cell of 500N of force. The elasticity variable did not present significant differences for the treatments, while the variables chewability, hardness, and firmness presented significant differences, with values between 0.00223333-0.336300 N for chewability, 0,2-1,9 N for Hardness, and 0,2-40,0 N for firmness. The best treatment is the vegetable meat with 10% potato starch. A sensorial analysis was also carried out with an acceptance sheet to 50 judges, where no significant differences were observed between the different treatments, revealing that all were slightly agreeable. Protein analysis was evaluated under the AOAC method, Ed.20.2016 for the best treatment. Vegetable meat with 10% potato starch added 15.16% protein.